Pimpinella katrajensis Rolla Rao et Hemadri- a New Species of Apiaceae from the Sahyadri Ranges Maharashtra State - Rao, Rolla Seshagiri; Hemadri, Koppula (Indian Forester, 1976)
Pimpinella katrajensisI Rolla Rao et Hemadri, a new species of Apiaceae collected from Katraj ghats (Poona district) and Mahabaleshwar. (Satara district) is described and illustrated.